Exposure to negative LGBT-related media messages as a social determinant of mental health inequities for LGBT+ people in Malaysia - Kyle, Tan; Shian Ling, Keng; Collin, Jerome; Wai Hsien, Cheah (Routledge Taylor & Francis, 2025)
commonplace in Malaysia. This study examines the prevalence of negative media exposure among LGBT+ people in Malaysia, the association between negative media exposure and mental health outcomes, and the role of negative future expectations for societal unacceptance as a mediator of the association. Method:  Drawing data from a cross-sectional survey of Malaysia-based LGBT+ adults (n=675; mean age = 27.78), we conducted a series of regression and mediation analyses to determine whether exposure to negative media messages was predictive of heightened levels of negative future expectations, depression, non-suicidal self-injury, and suicidality. Results: More than two-thirds (76%) saw negative LGBT-related messages regularly on newspapers, television, and social media in the past year. Frequent exposure of negative messages on media platforms was positively associated with depression, NSSI, and suicidal ideation. Negative future expectations partially mediated the relationship between exposure to negative messages and mental health outcomes. Conclusions:  The study highlights the role of negative media messages as a social determinant of mental health inequities for LGBT+ people. The findings call for a multi-level intervention to mobilize members in government sectors, healthcare settings, and academic institutions to discern and actively challenge disinformation targeting LGBT+ communities.